An Analysis of Sentence Types in Research Article Abstracts Written by English Education Students of UNP - Hasibuan, Siti Julya; Arianto, Muhammad Affandi (Journal of English Language Teaching, 2024)
Using sentence types in a research article, including in the abstract section, should be considered by students since it functions to show the quality of  research writing. An abstract is a summary of a research article that highlights the points and purpose, and it helps readers determine whether the article is relevant to their research interests. Thus, as a response to the function of sentence types, this research aimed to examine the sentence types in the abstract section using a qualitative approach and content analysis. This research employed Brandon’s theory (2011) of sentence types to see what sentence types were written by English education students of UNP in their research article abstracts. Then, 20 research article abstracts were used as the data of this research retrieved from JELT UNP, and the data were analyzed using a checklist table as an instrument. According to the result, it was found that not all types of sentences were used in every abstract. Simple sentences were used more frequently (67.5%) than complex sentences (28.1%) in abstracts. Compound sentences (3.1%) and compound-complex sentences (1.2%) were less common. Finally, this research has pedagogical significance for a better comprehension of academic writing, especially concerning the language use of a research article.